Strain and carrier transport along dislocations. Issue 8 (22nd July 2015) - Reiche, Manfred; Kittler, Martin; Pippel, Eckhard; Erfurth, Winfried; Haehnel, Angelika; Uebensee, Hartmut; Seibt, M.
Abstract A significant increase of the drain current is verified if defined numbers and types of dislocations are present in the channel of MOSFETs. For pMOSFETs, analysed here, an enhancement by a factor of eight exists if mixed dislocations are placed in the channel. The drain current increase is caused by higher concentration and higher mobility of holes on dislocations. It is shown that cores of mixed dislocations possess uniaxial compressive strain components in the order of ε ≅ –0.1 which are significantly higher than in the strain field surrounding a dislocation. The exceptional high uniaxial strain results in dramatic alterations of the silicon band structure. Upward shifts of the upper valence bands appear forming a quantum wire. The generation of the quantum wire forces hole confinement along dislocations and generates a one‐dimensional hole gas (1DHG). Confinement and energy quantization are assumed to be most important for the increased carrier transport along dislocations. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)